Studies on the Schismatoglottideae (Araceae) of Borneo VI : A New Schismatoglottis Species from Sarawak, Malaysian Borneo - Josef, Bogner; Peter C., Boyce (Singapore Botanic Garden, 2009)
Fieldwork in Sarawak continues to reveal further novelties in the genus Schismatoglottis Zoll & Moritzi, notably in the Asperata and Multiflora Groups (sensu Hay & Yuzammi, 2000). The second author collected a new Schismatoglottis species in Sarawak belonging to the Multiflora Group. This is here described and illustrated and included in additions to the key to Bornean Schismatoglottis published by Hay & Yuzammi (2000).